E-Book Development of Static Fluid Contents to Improve Students' Numeracy Literacy Competence - Muhammad Ziyyauddin Purwo Kartiko; Wahono Widodo; Madlazim Madlazim (Studies in Philosophy of Science and Education, 2022)
This study aims to develop an E-Book on Static Fluid Content in Tutoring as an educational partner to improve students' numeracy literacy competence. E-Book development is carried out using the 4-D development model which consists of defining, designing, developing, and disseminating stages. The research instruments used were E-Book validation sheets and questions that were tested on material expert lecturers and media expert lecturers from Surabaya State University. The validation results show that the E-Book developed has a very valid quality, with a validity percentage of 97%. Aspects of presentation feasibility, content feasibility and linguistic feasibility in the E-Book as a whole meet the criteria of "Very Valid" (85-100%) based on the validity interpretation table. In addition, the validity of the pre-test and post-test questions in the E-Book also proved high with a validity percentage of 89%. The questions measure students' ability to identify facts, formulate mathematical problems, use mathematical concepts, facts, procedures, and reasoning in the context of static fluids, carry out calculations based on certain rules or formulas, and interpret numeracy to solve problems. With the results of a high percentage of validity, this Static Fluid E-Book is reliable and feasible to use as teaching material media in improving students' numeracy literacy competencies. Interactive features in the E-Book, such as "Go Watch", "Mind Map", "Go Information", "Go Concept", "Problem Drilling", and "Reflection", provide interesting and diverse learning experiences for students in understanding static fluid concepts.